Priming methods affected deterioration speed of primed rice seeds by regulating reactive oxygen species accumulation, seed respiration and starch degradation - Ren, Muyao; Tan, Biao; Xu, Jiayi; Yang, Zhengpeng; Zheng, Huabin; Tang, Qiyuan; Zhang, Xiaoli; Wang, Weiqin (Frontiers in Plant Science, 2023)
Seed priming is a pre-sowing seed treatment that is beneficial for rice seed germination and seedling growth, but the reduced seed longevity after seed priming greatly limited its adoption. The deterioration of primed seeds showed large differences among different studies, and the priming method might play an important role in regulating the deterioration speed of primed seeds. However, whether and how the priming method affected the deterioration of primed rice seeds during storage remains unknown. In this study, two typical seed priming methods, namely hydropriming (HP) and osmopriming (PEG) were compared under artificially accelerated aging conditions, the changes in germination performance, starch metabolism, seed respiration and reactive oxygen species accumulation before and after accelerated aging were determined. The results showed that the hydroprimed rice seeds exhibited significantly faster deterioration speed than that of PEG-primed seeds in terms of germination speed and percentage. Meanwhile, α-amylase activity and total soluble sugar content in hydroprimed seeds were reduced by 19.3% and 10.0% respectively after aging, as compared with PEG-primed seeds. Such effects were strongly associated with the increased reactive oxygen generation and lipid peroxidation, as the content of superoxide anion, hydrogen peroxide and malondialdehyde in hydroprimed seeds were 4.4%, 12.3% and 13.7% higher than those in PEG-primed seeds after aging, such effect could be attributed to the increased respiratory metabolism in hydroprimed seeds. In addition, the simultaneous use of N-acetylcysteine with HP and PEG priming greatly inhibited the deterioration of primed rice seeds, suggesting that the ability to scavenge reactive oxygen species may be the key factor affecting the speed of deterioration in primed rice seeds during storage.